Linguistic competence in teaching syntax - Бакум, З. П. (Pedagogy of Higher and Secondary Education, 2011)
The ways of forming the students’ linguistic competence in the process of teaching of the syntax of the Ukrainian language are under consideration in the article; the system of work under the study of the syntactic units (wordform, word-combination, simple and complex sentence, text), their composition, the character of the component links.